(3cJGH GHf jhfS aj Gdabg GdeGdcis - (3GHf jhfSs
(3ChdgG (B:s
(3cJGH GdbPa heG ONdg ef cJGH GdQLe bGd GHf GdbGSe (B: (3hef TgO Ydjg CQHYI Cfg hWF gPg GdeQCI hdG jOQhf eG gi efg aYdjg GdMO s
(3BNQgG (B:s
(3aYdjc HgPg GdCNdGb Ef ESJWYJ , hdjS JWjb Pdc hdCNP Gdbdjd NjQ ef JQc GdcKjQ ced cJGH GdLGeY hgh BNQ GdOjhGf s
(3dbO JZjQ dhf HYV GdChQGb Edi GdMeQI GdeMJQbIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG CQVg , JQeje s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdabg GdeGdcjs